2021
DOI: 10.1002/cam4.4033
|View full text |Cite
|
Sign up to set email alerts
|

Regional and racial disparity in proximal gastric cancer survival outcomes 1996–2016: Results from SEER and China National Cancer Center database

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…As Kaplan-Meier curves illustrated, the prognosis of GCC patient in SEER database was worse than that of NGCC patients, while it was not the worst in the Chinese data, which was similar to previous studies [5,26]. Some researchers reported that these differences might be related to the surgical method and the number of lymph node resection [27,28], but more studies still required.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As Kaplan-Meier curves illustrated, the prognosis of GCC patient in SEER database was worse than that of NGCC patients, while it was not the worst in the Chinese data, which was similar to previous studies [5,26]. Some researchers reported that these differences might be related to the surgical method and the number of lymph node resection [27,28], but more studies still required.…”
Section: Discussionsupporting
confidence: 83%
“…In the past half century, the incidence of NGCC has decreased, which was replaced by the high incidence of GCC worldwide [3,4]. Black and white ethnicity with GCC had a higher mortality rate than yellow ethnicity, and the eastern region had a better prognosis than the western region globally [5]. It has been reported that the prognosis of GCC was potentially different from that of NGCC [6].…”
mentioning
confidence: 99%
“…27,28 There are significant regional differences in the incidence of some cancers in our country. 29,30 Hakka In this case-control study, the proportion of subjects with drinking and smoking history in the patients was higher than that in the controls. Overall, individuals in the control group had healthier lifestyles than those in patients.…”
Section: Discussionmentioning
confidence: 54%
“… 27 , 28 There are significant regional differences in the incidence of some cancers in our country. 29 , 30 Hakka population is one of the Chinese Han populations. Since the Song Dynasty, the Hakka ancestors who migrated southward from the central China began to live in the Hakka area in a relatively stable way, and merged with the local indigenous peoples and became Hakka.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation